Impact Of Educational Intervention On Community Pharmacists’ Knowledge, Attitude, And Practice Towards Antibiotic Resistance In Baghdad, Iraq: A Mixed-Method Approach - Kadhimi, Akram Hameed Majeed Al (2024)
Community pharmacists have a significant impact on the use of antibiotics. Mixed research methods were used to assess the dispensing pattern and practice of antibiotic in community pharmacy in Baghdad, Iraq. A qualitative study was conducted using face-to-face interviews to get in-depth understanding about the dispensing pattern and practice of antibiotics in community pharmacy. Thematic analysis was done and five themes were found to influence the dispensing practice of antibiotics in community pharmacy. Pharmacists' perception towards dispensing antibiotics without prescription was associated with medical condition, safety and efficacy of antibiotics, patients request antibiotics by name, emergency cases, regular customer, promotions from pharmaceutical companies, saving time and cost, medication brands, and poor healthcare services; in addition to inadequate knowledge about antibiotic resistance. Besides, quantitative study was conducted by performing a cross-sectional survey to assess knowledge, attitude, and practice regarding antibiotic resistance. Subjects were invited to participate in this study by using a convenience sampling approach. A self-administered questionnaire was used to obtain the data from 381 community pharmacists who took part in the preintervention assessment; and 338 in the post-intervention assessment.